Impacts on alternate bar geometry and dynamics in a trained sand bed river - Branß, Till; Aberle, Jochen; Hentschel, Bernd (Frontiers in Water, 2023)
This study investigates the occurrence and dynamics of single row alternate bars forming in a particular reach of the sand bed Elbe River in Germany. Although the formation and dynamics of alternate bars have been intensively investigated in the literature, there exists only a limited number of studies focusing on the characteristics of alternate bars forming under complex field conditions. This is particular the case for bars forming in trained sand bed rivers, as most previous field studies have focused on gravel bed rivers. Moreover, little is known on the impact of river training structures on bar characteristics in anthropogenic rivers. To close this gap, we present a comprehensive bed elevation data set that was collected over a period of 10 years within a 30 km long reach of the lower Elbe River in Germany by the Federal Waterways and Shipping Administration (WSV). The reach is characterized by a sand bed, has curved as well as straight parts, and exhibits a section that is less trained by groynes than the neighboring sections. For our analyses, we propose a novel approach to estimate bar characteristics based on statistically derived geometrical parameters. The outcomes of the approach are used to show that bars in Elbe River belong to the free bar type and that their origin of formation and characteristics depend on hydrological and geometrical boundary conditions. The results reveal that the active width of the river bed, defined as the distance between the groyne heads, is a crucial parameter for the occurrence of alternate in the reach. We further highlight the impact of river bends on bar characteristics, as bars in the outer bend were longer and higher than their inner bend counterparts. Finally, we show that simple predictors for bar formation can be successfully applied to predict bar formation in sand bed rivers but that care needs to be taken when applying such approaches to more complex boundary conditions.